Factors Affecting Working Memory Capacity: a Meta-Analysis Study - Fika Tri Anggraini (Jurnal Penelitian Pendidikan IPA, 2023)
Working memory capacity (WMC) is a brain memory system that has a limited ability to process and store temporary information. The purpose of this study was to find out in more detail the factors affecting working memory capacity. The research method uses Meta-analysis quantitatively by combining several research results using Jeffreys's Amazing Statistics Program (JASP) software. The size of the effect used is the odds ratio. Research search using Prisma strategy by searching journal articles from various databases including Scopus, Proquest, Science Direct, CINAHL, and Google Scholar in the last five years from 2019 to 2023. Results Variation between variables is heterogeneous, so this meta-analysis uses a random-effect model, obtained results there is an influence between age on working memory capacity with a combined effect of OR= 3.15 (95% CI 2.10; 4.20), there is an effect of sleep quality on working memory capacity with a combined effect of OR= 6.45 (95% CI 3.51; 9.39), there is an effect of physical activity on working memory capacity with a combined effect of OR=2.84 (1.98; 3.11),Â  there was an effect of listening to music on working memory capacity with a combined effect of OR=3.24 (2.65; 5.13). In conclusion, age, sleep quality, physical activity, and music are factors that affect working memory capacity.